Pengoperasian Alat Produksi Metana dari Pembakaran Limbah Kulit Padi - Yoyo Saputro (Accurate: Journal of Mechanical Engineering and Science, 2020)
This study aims to obtain the design and operation of methane (CH4) production equipment from burning of rice husk waste by burning it in a burner setup (testing) and to determine the effect of variations in air mass flow on the combustion temperature of rice husk waste, boiling time of water, and burning time maximum, combustion temperature. In this study using air mass flow of 0.020 m3 / s, 0.022 m3 / s, and 0.024 m3 / s, data collection included burning 5 kg of rice husk waste, boiling water volume, maximum flame time, combustion temperature. The results of the production of methane scale mass flow production tools have an effect on the effective flame and heat value. Or it can be concluded that the lower the mass of air mass used the longer the maximum flame produced, so that the heat obtained is also greater.